ENHANCING THE DEVELOPMENT OF THE NATIVE LANGUAGE AND IMPROVING LINGUISTIC COMPETENCE IN OUR COUNTRY (Prima Journal of Integrated Studies, 2026)
This article analyzes the importance of enhancing the development of the native language and improving linguistic competence in the context of globalization. It examines the role of education, technology, media, and government policies in strengthening language use. The study also identifies existing challenges and proposes effective strategies for preserving and developing the native language in modern society.
Keywords: Native language, linguistic competence, language development, education system, language policy, globalization, cultural heritage, communication, language culture.